The capital budgeting techniques practices on TNB: a case study of TNB Banda Kaba Melaka / Mohd Razif Karim - Karim, Mohd Razif (Faculty of Business and Management, 2010)
This case study is capital budgeting techniques practices toward TNB Banda Kaba. The techniques in the study have seven techniques. There are payback period, discounted payback period, net present value, average/accounting rate of return, internal rate of return, profitability index, and modified rate of return. But at TNB Banda Kaba only use five techniques. There are payback period, discounted payback period, average/accounting rate of return, internal rate of return, and net present value. Two techniques are not concerned in the TNB Banda Kaba in their capital budgeting practices.